RESHORING IN MANUFACTURING AND SERVICES - Serghei MĂRGULESCU; Elena MĂRGULESCU (Challenges of the Knowledge Society)
The extent of offshoring and outsourcing recorded in manufacturing and services in the last two decades has gradually eroded the advantage of the global arbitrage of labor costs. Along with other factors, this process began to change the options of international relocation of some companies that initially had adopted such a strategy, generating a reverse trend for returning in the country of origin of manufacturing and other activities. This process, called "reshoring," has recently started to gain some consistency. The trend is most notable in the sphere of production. In terms of business and IT services we cannot yet speak of a tangible start of the reshoring phenomenon, as it does in the sphere of production. Nevertheless we can see a slowdown in the offshoring of services and the emergence of new strategies in the field.